Hale inżyniera Gottfrieda - Anna Syska (Miejsce)
The originality of Jerzy Gottfried’s designs stands out in the landscape of Upper Silesia, achieved with untypical steel and reinforced concrete structures. The architect initially worked at the Miastoprojekt in Katowice with Henryk Buszko and Aleksander Franta. Having withdrawn from that collaboration, Gottfried developed an individual practice involving the design of exhibition and sports halls, executed later in collaboration with engineer Włodzimierz Feiferek. The halls were intended to be low-cost and quick to build. The structures resemble buildings raised in the West, but the designer admits nothing but inspiration: ‘We only heard the echoes, that a hall was being built somewhere in Europe, but we knew nothing about its structure and what exactly it looked like. We could not travel, technology in Poland was crap. We knew the motto, like a song title, but we later needed to write the song anew with the means available to us in Poland.’